2015
DOI: 10.7314/apjcp.2015.16.11.4665
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation of RASSF1A gene Contribute to the Risk of Renal Cell Carcinoma: a Meta-Analysis

Abstract: The aim of this study was to assess the diagnostic value of RASSF1A methylation in renal cell carcinoma. Systematically search were performed using the Pubmed, ProQest and Web of Science for all articles on the association between RASSF1A methylation and renal cell carcinoma before 15 April 2015. After the filtration, 13 studies involving 677 cases and 497 controls met our criteria. Our meta-analysis suggested that hypermethylation of RASSF1A gene was associated with the increased risk of RCC(OR:4.14, 95%CI:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…The current results compare favorably with the previous meta-analyses by Yu et al48 and Huang et al49 Yu et al only analyzed whether RASSF1A promoter methylation was correlated with RCC in cancer vs nontumor controls,48 and RASSF1A promoter methylation did not correlate with RCC in tissue samples 48. Our result involving a greater number of eligible studies with a larger population (15 studies with 1,296 tissue samples) showed that RASSF1A promoter methylation was significantly associated with RCC in tissue samples.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current results compare favorably with the previous meta-analyses by Yu et al48 and Huang et al49 Yu et al only analyzed whether RASSF1A promoter methylation was correlated with RCC in cancer vs nontumor controls,48 and RASSF1A promoter methylation did not correlate with RCC in tissue samples 48. Our result involving a greater number of eligible studies with a larger population (15 studies with 1,296 tissue samples) showed that RASSF1A promoter methylation was significantly associated with RCC in tissue samples.…”
Section: Discussionsupporting
confidence: 91%
“…Our result involving a greater number of eligible studies with a larger population (15 studies with 1,296 tissue samples) showed that RASSF1A promoter methylation was significantly associated with RCC in tissue samples. In addition, Yu et al48 did not report whether RASSF1A promoter methylation was linked to clinical features (eg, gender, tumor grade, clinical stage, T classification, histologic subtypes, lymph node metastasis, and distant metastasis) and did not include an analysis of overall survival. Huang et al only analyzed whethe RASSF1A promoter methylation was linked to tumor stage (five studies with 252 cases) and grade (four studies with 190 cases), showing that RASSF1A promoter methylation had a borderline significant correlation with tumor stage ( P =0.051) and a significant association with tumor grade ( P =0.001) 49.…”
Section: Discussionmentioning
confidence: 99%
“…Unexpectedly, when we assessed hypermethylation of RASSF1A promoter region in ccRCC, we found a relatively low number of hypermethylated tumor samples, probably due to high DNA heterogeneity in ccRCC tissue as observed by other groups ( 19 , 20 ). Although other authors reported high association of RASSF1A methylation with increased risk of RCC, it has to be noted that this was attributed only to serum DNA but not cancer tissue ( 21 ). In the present study probably the more homogeneous histology of twelve ccRCC metastasized samples resulted in the increased OR similarly to data on serum DNA ( 22 24 ).…”
Section: Discussionmentioning
confidence: 94%
“…E2, is known to exert a protective effect beyond its classical endocrine role in several malignant diseases including neurodegenerative disorders, esophageal cancers, colorectal cancers, lung injuries, and coronary artery diseases [ 11 , 40 , 42 , 46 ]. Many cellular functions can be improved by treatment with E2 alone or in combination with its receptors [ 3 , 25 ].…”
Section: Introductionmentioning
confidence: 99%